2020
DOI: 10.1093/cdn/nzaa118
|View full text |Cite
|
Sign up to set email alerts
|

Tracking of Maternal Diet from Pregnancy to Postpregnancy: A Systematic Review of Observational Studies

Abstract: We systematically reviewed studies to examine changes in women's diets from pregnancy to post-pregnancy period and sought to understand the characteristics of women making these changes. From a search of 4 databases and up to November 2019, 17 studies met our inclusion criteria. They reported changes in various dietary aspects. Mixed findings were reported for changes in energy and micronutrient intakes. Most studies reported significant decreases in fruit and vegetable consumption, diet quality and adherence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 82 publications
0
22
0
1
Order By: Relevance
“…There is generally a decline in healthy dietary behaviours from pregnancy through to postpartum [ 29 , 30 , 31 ] ( Table 1 ). Diet quality was reported to be higher in the first postpartum year compared to subsequent years indicating that the decline in diet quality continues even after the first postpartum year [ 31 ].…”
Section: Predictors Of Postpartum Weight Retentionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is generally a decline in healthy dietary behaviours from pregnancy through to postpartum [ 29 , 30 , 31 ] ( Table 1 ). Diet quality was reported to be higher in the first postpartum year compared to subsequent years indicating that the decline in diet quality continues even after the first postpartum year [ 31 ].…”
Section: Predictors Of Postpartum Weight Retentionmentioning
confidence: 99%
“…Diet quality was reported to be higher in the first postpartum year compared to subsequent years indicating that the decline in diet quality continues even after the first postpartum year [ 31 ]. Lee et al’s review reported less adherence to healthier dietary patterns, specifically decreased fruit and vegetable intake and increased intake of energy dense and nutrient poor food during the transition from pregnancy to postpartum [ 30 ]. This worsening of lifestyle behaviours in the postpartum period could be due to the demands associated with caring for a child [ 32 ].…”
Section: Predictors Of Postpartum Weight Retentionmentioning
confidence: 99%
“…44,45 Furthermore, a recent systematic review reported that overall maternal diet quality declined during the transition from pregnancy to postpartum, with the majority of studies reported significant decreases in fruit and vegetable consumption, and an increase in discretionary foods and high fat intakes observed. 46 These results demonstrate that young women consume suboptimal dietary intakes of core food groups including fruits and vegetables, legumes, nuts, whole grains, dairy, seafood/plant protein, and excessive intake of foods and beverages high in saturated fat and added sugars that further deteriorates from pregnancy to postpartum. Subsequently, nutrient intake levels for folate, fiber, iron, calcium, magnesium, vitamin D, and vitamin E were below recommended levels, indicating that many young women may be nutritionally unprepared for pregnancy.…”
Section: Diet Quality In Young Womenmentioning
confidence: 88%
“…Further, diet quality was only assessed during pregnancy and should be assessed during lactation, preferably at multiple timepoints, as it is likely that maternal diet changes post pregnancy. The literature points to a decrease in overall diet quality (along with fruit and vegetable intake), and an increase in the intake of energy-dense yet nutrient-poor food choices post pregnancy [ 41 ].…”
Section: Discussionmentioning
confidence: 99%